A new species of Tophoderes Dejean from northern Madagascar with a checklist of the species (Coleoptera: Anthribidae) - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2015)
A new species, Tophoderes lidmilae Trýzna & Baňař sp. nov., from north Madagascar is described. Male genitalia are studied and illustrated and colour photographs of both sexes are added. A comparison with the most similar known species T. frenatus (Klug, 1833) is provided. A checklist of species of the Madagascan genus Tophoderes (Anthribidae: Anthribinae: Tophoderini) is provided.